2023
DOI: 10.7759/cureus.37522
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction Signs and Symptoms: Females vs. Males

Abstract: Cardiovascular disease is the number one killer of females in the United States today, and myocardial infarction (MI) plays a role in many of these deaths. Females also present with more "atypical" symptoms than males and appear to have differences in pathophysiology underlying their MIs. Despite both differences in symptomology and pathophysiology being present in females versus males, a possible link between the two has not been studied extensively. In this systematic review, we analyzed studies examining di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…This study demonstrated significant disparities in patient characteristics between the 2 groups. Overall, there were more male patients with STEMI in both of our cohorts, which can be attributed to the well-documented difference in the prevalence of myocardial infarction between sexes [ 18 ]. However, when looking at each subgroup, there was a higher proportion of females seen in the sarcoidosis group compared to the non-sarcoidosis group.…”
Section: Discussionmentioning
confidence: 94%
“…This study demonstrated significant disparities in patient characteristics between the 2 groups. Overall, there were more male patients with STEMI in both of our cohorts, which can be attributed to the well-documented difference in the prevalence of myocardial infarction between sexes [ 18 ]. However, when looking at each subgroup, there was a higher proportion of females seen in the sarcoidosis group compared to the non-sarcoidosis group.…”
Section: Discussionmentioning
confidence: 94%
“…The early detection and treatment of hypercholesterolemia is crucial to prevent atherosclerosis development ( 34 ), especially in males. Indeed, they have a higher incidence of myocardial infarction than females, with males accounting for approximately 70% of infarctions and having a myocardial infarction 7–10 years earlier than females ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to gender disparity in cardiovascular care, where females remain underdiagnosed and undertreated in comparison to their male counterparts [48,49]. Another possible explanation of male predominance can lie in the pathophysiological differences between males and females, with females typically exhibiting a lesser extent of arterial plaque buildup, known as atherosclerotic burden, compared to men during a myocardial infarction (MI) [50]. Elevated microvascular resistance has been associated with unrecognized myocardial infarction (MI) in women, and after menopause, women are more likely to experience higher rates of resistance in their coronary microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated microvascular resistance has been associated with unrecognized myocardial infarction (MI) in women, and after menopause, women are more likely to experience higher rates of resistance in their coronary microvasculature. These alterations in the microvasculature due to aging and menopause might contribute to women experiencing more unusual symptoms that often remain undetected [50]. These variations between males and females warrant further research to better understand their potential implications for clinical practice, ultimately aiming to optimize cardiovascular care for individuals of all genders.…”
Section: Discussionmentioning
confidence: 99%